Prevalence of hepatitis D virus infection in sub-Saharan Africa: a systematic review and meta-analysis - Stockdale, Alexander J (Lancet Glob Health, 2017)
BACKGROUND: Hepatitis D virus (also known as hepatitis delta virus) can establish a persistent infection in people with chronic hepatitis B, leading to accelerated progression of liver disease. In sub-Saharan Africa, where HBsAg prevalence is higher than 8%, hepatitis D virus might represent an important additive cause of chronic liver disease. We aimed to establish the prevalence of hepatitis D virus among HBsAg-positive populations in sub-Saharan Africa. METHODS: We systematically reviewed studies of hepatitis D virus prevalence among HBsAg-positive populations in sub-Saharan Africa. We searched PubMed, Embase, and Scopus for papers published between Jan 1, 1995, and Aug 30, 2016, in which patient selection criteria and geographical setting were described. Search strings included sub-Saharan Africa, the countries therein, and permutations of hepatitis D virus. Cohort data were also added from HIV-positive populations in Malawi and Ghana. Populations undergoing assessment in liver disease clinics and those sampled from other populations (defined as general populations) were analysed. We did a meta-analysis with a DerSimonian-Laird random-effects model to calculate a pooled estimate of hepatitis D virus seroprevalence. FINDINGS: Of 374 studies identified by our search, 30 were included in our study, only eight of which included detection of hepatitis D virus RNA among anti-hepatitis D virus seropositive participants. In west Africa, the pooled seroprevalence of hepatitis D virus was 7·33% (95% CI 3·55–12·20) in general populations and 9·57% (2·31–20·43) in liver-disease populations. In central Africa, seroprevalence was 25·64% (12·09–42·00) in general populations and 37·77% (12·13–67·54) in liver-disease populations. In east and southern Africa, seroprevalence was 0·05% (0·00–1·78) in general populations. The odds ratio for anti-hepatitis D virus detection among HBsAg-positive patients with liver fibrosis or hepatocellular carcinoma was 5·24 (95% CI 2·74–10·01; p<0·0001) relative to asymptomatic controls. INTERPRETATION: Findings suggest localised clusters of hepatitis D virus endemicity across sub-Saharan Africa. Epidemiological data are needed from southern and east Africa, and from patients with established liver disease. Further studies should aim to define the reliability of hepatitis D virus testing methods, identify risk factors for transmission, and characterise the natural history of the infection in the region. FUNDING: Wellcome Trust, Royal Society.